Past and present currency board experiments in Argentina - Pérex, Esteban (Caribbean Centre for Money & Finance [St. Augustine]TT, 2002)
Analyzes abnd compares two currency board experiments carried out in Argentina in two diffenent time periods 1899-1914 and 1991-2001.